DIALECT VARIATIONS IN MANGKOBAR AT WEDDING CEREMONY IN SOUTH TAPANULI - Imelda Pandiangan; Juli Rachmadani Hasibuan; Sisilia Fitriani Damanik (LINGUISTICA, 2019)
The study deals with the aspects of dialect inmangkobarat wedding ceremony in South Tapanuli. The objectives of the study are to describe the aspects of dialect and to know the reasons the differences of dialect that occurred in mangkobar at wedding ceremony in South Tapanuli. The method that used in this study is descriptive qualitative.  The data were analysed by  identifying the transcribed from the  utterances of pakkobarin wedding ceremony from two sub-districts. The findings show that the three aspects in dialect are occurred in mangkobar. There are 22 words are different in phonological, 35 words are different in lexem and 3 sentences are different in grammatical. And the reasons of the differences the language used in mangkobarat wedding ceremony in South Tapanuli are social conflict and geographical origin. Keywords:Dialect, Regional dialect, Mangkobar, South Tapanuli